MENYOAL EKSISTENSI KELEMBAGAAN MANAJEMEN INOVASI PERGURUAN TINGGI DALAM HAL HILIRISASI HASIL RISET - Muh Ali Masnun; Dilla Nurfiana Astanti (STIH Putri Maharaja, 2020)
Research as one of the important pillars for the progress of a nation, it is because the outcome of research can be transferred to the user. The purpose of this study is to examine the existence of innovation management institutions in higher education in the case of transfering of research results after the promulgation of the Ministry of Research and Technology MIPTi in 2019. This study uses legal research methods using primary and secondary legal materials. The approach used is the legislative approach and institutional approach for in-depth analysis. The results showed several things including, firstly that the existence of innovation management institutions from the normative side was still relatively weak, it was based on provisions which were still optional to open space for universities to not manage innovation management optimally. Second, that normatively it has not been explained in detail, especially related to institutional aspects and practice guidelines for most of the functions to be carried out by the innovation management agency. Third, that from the normative side the authority of the innovation management agency has the potential to overlap with the authority of the intellectual property center. The recommendation for this research is that there needs to be a strict regulation on the existence of an innovation management institution and harmonization of an innovation management agency with other laws and regulations.